Proceedings of the 2016 ACM Conference on Economics and Computation 2016
DOI: 10.1145/2940716.2940731
|View full text |Cite
|
Sign up to set email alerts
|

Truthful Outcomes from Non-Truthful Position Auctions

Abstract: In the standard single-dimensional model of position auctions, bidders agree on the relative values of the positions and each of them submits a single bid that is interpreted in terms of these values. Motivated by current practice in sponsored search we consider a situation where the auctioneer uses estimates of the relative values, which may be imprecise, and show that under both complete and incomplete information a non-truthful mechanism is able to support an efficient outcome in equilibrium for a wider ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The first results we present regard how well our heuristic ad allocation algorithm approximates the optimal solution. 6 We report results on a random selection of 100,000 auction instances drawn from Yahoo's Gemini search platform for Desktop devices. An "instance" consists of a set of candidate ads and all relevant accompanying information (bids, clickability predictions, size, decorations, etc.).…”
Section: Allocation Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…The first results we present regard how well our heuristic ad allocation algorithm approximates the optimal solution. 6 We report results on a random selection of 100,000 auction instances drawn from Yahoo's Gemini search platform for Desktop devices. An "instance" consists of a set of candidate ads and all relevant accompanying information (bids, clickability predictions, size, decorations, etc.).…”
Section: Allocation Accuracymentioning
confidence: 99%
“…As discussed, to precisely compute prices (say, according to Eq. (6) or Eq. (7)) one needs to compute the allocation curve for the bidder, from which the price can be quickly deduced.…”
Section: Pricing Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Initial analyses showed that revenue and welfare in reasonable equilibria are no worse than VCG [Varian, 2007, Edelman et al, 2007. Later studies offered more nuanced analyses -a more recent justification falls out of GSP's simplicity: GSP's equilibrium guarantees are immune to certain errors in click modeling [Milgrom, 2010, Dütting et al, 2016. Unfortunately, none of these results would guide us to invent GSP if it weren't already implemented in practice.…”
Section: A Generalizable Definition Of Gspmentioning
confidence: 99%
“…Our collective first response was simply "it can't be too bad:" revenue and welfare in reasonable equilibria are no worse than VCG [27,17]. Many studies of GSP followed -a more recent justification falls out of GSP's simplicity: GSP pricing is independent of the likelihood that the user clicks on an ad, 2 so GSP's equilibrium guarantees are immune to errors in click modeling [22,15]. Yet, throughout these and many other results, the community's implicit perspective has remained constant: GSP is an ugly duckling that requires continual excuses.…”
Section: Introductionmentioning
confidence: 99%